Developing Solution-Processed Distributed Bragg Reflectors for Microcavity Polariton Applications - Palo Emilia; Papachatzakis Michael A. A.; Abdelmagid Ahmed; Qureshi Hassan; Kumar Manish; Salomäki Mikko; Daskalakis Konstantinos S. S. (AMER CHEMICAL SOC, 2025)
Improving the performance of organic optoelectronicshas been undervigorous research for decades. Recently, polaritonics has been introducedas a technology that has the potential to improve the optical, electrical,and chemical properties of materials and devices. However, polaritonshave been mainly studied in optical microcavities that are made byvacuum deposition processes, which are costly, unavailable to many,and incompatible with printed optoelectronics methods. Efforts towardthe fabrication of polariton microcavities with solution-processedtechniques have been utterly absent. Herein, we demonstrate for thefirst time strong light-matter coupling and polariton photoluminescencein an organic microcavity consisting of an aluminum mirror and a distributedBragg reflector (DBR) made by sequential dip coating of titanium hydroxide/poly(vinylalcohol) (TiOH/PVA) and Nafion films. To fabricate and develop thesolution-processed DBRs and microcavities, we automatized a dip-coatingdevice that allowed us to produce sub-100 nm films consistently overmany dip-coating cycles. Owning to the solution-based nature of ourDBRs, our results pave the way to the realization of polariton optoelectronicdevices beyond physical deposition methods.